2015
DOI: 10.3390/en8099407
|View full text |Cite
|
Sign up to set email alerts
|

Can the BestGrid Process Improve Stakeholder Involvement in Electricity Transmission Projects?

Abstract: Abstract:The European Union has set ambitious targets for deployment of renewable energy sources to reach goals of climate change mitigation and energy security policies. However, the current state of electricity transmission infrastructure is a major bottleneck for further scaling up of renewable energy in the EU. Several thousands of kilometers of new lines have to be constructed and upgraded to accommodate growing volumes of intermittent renewable electricity. In many countries, construction of electricity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…[50,17]), however, in our empirical material, local resistance does not appear as a key regime barrier for grid development. This aligns with Sataøen et al [68] who saw that Sweden, maybe surprisingly and in contrast to the UK and Norway, experiences less public resistance than its neighbouring countries.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…[50,17]), however, in our empirical material, local resistance does not appear as a key regime barrier for grid development. This aligns with Sataøen et al [68] who saw that Sweden, maybe surprisingly and in contrast to the UK and Norway, experiences less public resistance than its neighbouring countries.…”
Section: Discussionmentioning
confidence: 94%
“…In the social sciences, a body of research on local public resistance to grid development has emerged (e.g [4,9,17,44,49,50,68], whereas research into grid politics, planning, and governance at national and international level has been scarce (but see [8,13,64]. This paper aims to contribute to the latter body of work and also to the research agenda suggested by Sovacool [74] and Puka and Szulecki [64] on the underlying social explanations behind the too-slow development of the transmission grid in many places, despite the widely agreed benefits of it.…”
Section: Introductionmentioning
confidence: 99%
“…For example, suitable alternatives on how and where to implement different types of projects can be negotiated between industries and local communities. However, in reality there seems to be some kind of a "Decide-Announce-Defend" model that is still dominating the process and communication between different stakeholders, as it has been shown by studies of Battaglini et al (2012), Komendantova et al (2015), and Komendantova and Battaglini (2016).…”
Section: Participatory Governancementioning
confidence: 99%
“…Komendantova et al [28] examine the concerns of local stakeholders affected by the construction of electricity transmission infrastructure. Since several thousands of kilometers of new lines have to be constructed and upgraded at the European level to accommodate growing volumes of intermittent renewable electricity, the dialogue between transmission system operators and non-governmental organizations, as exemplified by the BestGrid approach, is crucial.…”
Section: A Short Review Of the Contributions In This Issuementioning
confidence: 99%